2016
DOI: 10.4137/ccrep.s39776
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Voluntary Starvation of 50 Days

Abstract: A 34-year-old obese male (96.8 kg; BMI, 30.2 kg m−1) volitionally undertook a 50-day fast with the stated goal of losing body mass. During this time, only tea, coffee, water, and a daily multivitamin were consumed. Severe and linear loss of body mass is recorded during these 50 days (final 75.4 kg; BMI, 23.5 kg m−1). A surprising resilience to effects of fasting on activity levels and physical function is noted. Plasma samples are suggestive of early impairment of liver function, and perturbations to cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An average body mass should provide fats for up to approximately two months to assist the starved individual in surviving the threat of starvation [ 202 ]. As a result, individuals who are trapped in a confined area with food deprivation will survive for up to 60 days, depending on access to water and their body mass.…”
Section: Discussionmentioning
confidence: 99%
“…An average body mass should provide fats for up to approximately two months to assist the starved individual in surviving the threat of starvation [ 202 ]. As a result, individuals who are trapped in a confined area with food deprivation will survive for up to 60 days, depending on access to water and their body mass.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some individuals could survive continual no-food fasting from 40days [5,6] or even more than a year [7,8]. Historical books from China and India also record some examples of months to years of absolutely no food status (bigu) as a way to attain longevity and spiritual distillation [9,10].…”
Section: Background Motivation and Objectivesmentioning
confidence: 99%
“…It has been reported that some individuals could survive continual no-food fasting from 40 days (5,6) or even more than a year (7,8). Historical books from China and India also record some examples of months to years of absolutely no food status (bigu) as a way to attain longevity and spiritual distillation (9, 10).…”
Section: Background Motivation and Objectivesmentioning
confidence: 99%